EXPLORING THE POTENTIAL OF MAKING TRADITIONAL SEMPRONG CAKES IN JAMBON VILLAGE - Dwi Astono, Ari; Firdaus, Firdaus; Amalia Wulandari, Nisa; Felda, Elina (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
Community service carried out with the need to increase income and create jobs, as well as preserving local cultural identity through traditional culinary heritage, aims to increase the production of semprong cakes in Jambon Village, Temanggung Regency. The main aim of the service is to increase income and create jobs in the village, as well as to strengthen local cultural identity and preserve traditional culinary heritage. The implementation method uses PAR (Participatory Action Research) involving training and mentoring carried out by the PKM Team and students of the Muhammadiyah University of Semarang (Unimus). Concrete results from this service include developing more effective marketing strategies and improving the quality of semprong cake production. Culturally, this increase in production plays a role in preserving local wisdom and transmitting culinary traditions to future generations. In addition to direct benefits for village communities, this program also provides valuable insight into the social, economic and cultural conditions of local communities. Thus, this service has the potential to become a model of sustainable local development and can be applied in other areas that have similar potential.